Peripheral and central pathogenesis of postherpetic neuralgia - Liu, Qiuping; Han, Jingxian; Zhang, Xuezhu (Skin research and technology, 2024)
Background Postherpetic neuralgia (PHN) is a classic chronic condition with multiple signs of peripheral and central neuropathy. Unfortunately, the pathogenesis of PHN is not well defined, limiting clinical treatment and disease management. Objective To describe the peripheral and central pathological axes of PHN, including peripheral nerve injury, inflammation induction, central nervous system sensitization, and brain functional and structural network activity. Methods A bibliographic survey was carried out, selecting relevant articles that evaluated the characterization of the pathogenesis of PHN, including peripheral and central pathological axes. Results Currently, due to the complexity of the pathophysiological mechanisms of PHN and the incomplete understanding of the exact mechanism of neuralgia. Conclusion It is essential to conduct in‐depth research to clarify the origins of PHN pathogenesis and explore effective and comprehensive therapies for PHN.